Revolutionizing learning: Enhancing student worksheets on plant tissue structure through vee diagrams in alignment with the merdeka curriculum - Saputra, Angga Dwi; Supriatno, Bambang (Department of Biology Education, Universitas Pendidikan Indonesia, 2024)
Practicum is an important component in biology learning and it helps students to gain hands-on experience. Practicum activities can be provided with the help of student worksheets. Based on observations, the student worksheets used have inadequate quality. This study aims to analyze and reconstruct the student worksheets. The research method applied in this study is a qualitative descriptive method. With the following flow: Analysis, Try, and Reconstruction. The results of the analysis using the Laboratory Activity Analysis Form show that there are problems in the student worksheets Plant Tissue Structure from a structural aspect. Problems were also found in conceptual, practical specifications and knowledge construction specs through vee diagram analysis. Therefore, reconstruction was carried out on the student worksheets Structure and Function of Plant Tissues. The reconstructed worksheets were developed according to the demands of an independent curriculum that emphasizes students' literacy and numerical reasoning skills. The practical aspect of the worksheets aimed to guide students in discovering factual objects and phenomena through hands-on activities, thereby facilitating the construction of knowledge.